Modelagem de espaços inteligentes pessoais e espaços inteligentes fixos no contexto de cenários de computação ubíqua - Vieira, Marcos Alves (2016)
Advances in electronics allow the creation of everyday devices with computing capabilities, called smart objects. Smart objects assist people in carrying out a variety of tasks and compose smart spaces. When smart spaces are confined to a certain area, they can be referred to as fixed smart spaces. In complement of these, personal smart spaces are composed by the smart objects a user carries with himself, hence with boundaries moving along with his owner. However, user mobility and the increasing number of smart spaces, fostered also by the Internet of Things (IoT) and the Web of Things (WoT), can lead to smart spaces overlap, where a certain smart object is configured in different smart spaces, whether fixed or personal. In addition, smart spaces are complex and difficult to model and maintain, as, among other factors, they have to deal with different smart objects. This thesis proposes the use of Model-Driven Engineering to enable modeling of ubiquitous computing scenarios, considering the coexistence between fixed and personal smart spaces. Its contributions include a metamodel for modeling scenarios composed by personal smart spaces and fixed smart spaces, together with a language and an algorithm, aiming at determining the access order to the resources of a ubiquitous computing scenario. The validation of the proposal was carried out based on the results of a Systematic Literature Review, conducted in order to identify metamodel validation methods most commonly used by researchers within the field. Thus, scenarios were modeled with the aid of modeling tools, which were constructed to produce models, conforming to the proposed metamodels. An implementation in Java enabled to validate the access policy language as well as its processing algorithm.